Minuman Probiotik dari Limbah Kulit Nanas sebagai Upaya Peningkatan Imunitas dalam Pencegahan Covid-19 di Kelompok PKK RT.06/RW.03 Rungkut Barata Surabaya - riski ayu anggreini; noni rahmadhini; laksmi diana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Covid-19 has been declared as pandemic and has spread in 216 countries around the world. WHO’s distribution data obtained on May 31, 2020 that there were 5,891,182 positive cases of Covid-19 in the world with 365,966 deaths. The condition in Indonesia is classified as serious as well, which 25,773 positive cases with 1,573 deaths. Covid-19 has the potential to attack humans with poor immunity, so that a healthy lifestyle plays a role in increasing endurance, such as eating healthy food like probiotics. One of the media that can be used to grow probiotics is pinneapple peel. The community service partner was PKK RT. 06/RW.03 Rungkut Barata residents, the majority of whom are middle aged and elderly. This age is classified as vulnerable to being exposed to Covid-19, so in this acrivity we plan to carry out activity related to probiotics by utillizing pineapple skin waste. Futhermore, the location of the partners is strategic because near the market and sorrounded by several pineapple sellers. The method activity was preparation and coordination with the partner, then continues with conselling and training on making probiotic product. The output was probiotic product, training moduls and documentation.